Interface characterization of CO2 laser welded austenitic stainless steel and low carbon steel couple - Caligulu, Ugur; Taskin, Mustafa; Kejanli, Haluk; Orhan, Ayhan (Emerald Group Publishing Ltd, 2012)
Purpose - The purpose of this paper is to investigate interface characterization of CO2 laser welded AISI 304 austenitic stainless steel and AISI 1010 low carbon steel couple. Laser welding experiments were carried under argon and helium atmospheres at 2000, 2250 and 2500 W heat inputs and 200-300 cm/min welding speeds. Design/methodology/approach - The microstructures of the welded joints and the heat affected zones (HAZ) were examined by optical microscopy, SEM, EDS and X-Ray analysis. The tensile strength of the welded joints was measured. Findings - The result of this study indicated that the width of welding zone and HAZ became much thinner depending on the increased welding speed. On the other hand, this width widened depending on the increased heat input. Tensile strength values also confirmed this result. The best properties were observed at the specimens welded under helium atmosphere, at 2500 W heat input and at 200 cm/min welding speed. Originality/value - There are many reports which deal with the shape and solidification structure of the fusion zone of laser beam welds in relation to different laser parameters. However, the effect of all influencing factors of laser welding has up to now not been extensively researched. Much work is required for understanding the combined effect of laser parameters on the shape and microstructure of the fusion zone. This paper, therefore, is concerned with laser power, welding speed, defocusing distance and type of shielding gas and their effects on the fusion zone shape and final solidification structure of some stainless steels.
Keywords: Stainless steel; Welding; Joining processes; Austenitic stainless steel; Low carbon steel; CO2 laser welding; Interface characterization